In-silico characterization of cadmium stress response-associated Abc1-like protein and its homologues in maize (Zea mays) - Singh, Alla; Karjagi, Chikkappa; Kumar, Ramesh; Chaudhary, D P; Rakshit, Sujay (The Indian Journal of Agricultural Sciences, 2020)
Cadmium is a pollutant of concern and accumulates in soil from unchecked industrial activities like smelting, incinerations and combustion. Plants interact via different mechanisms with heavy metal pollutants in soil. Understanding of the plant-soil-metal interactions and the biomolecules involved in this interaction is important to make informed choices for setting breeding goals. In Arabidopsis thaliana, AtOSA1 (A. thaliana oxidative stress-related Abc1-like protein) is involved in response to cadmium stress. The homologous sequences have been deciphered in maize (Zea mays L.). The structures of the maize proteins have been determined. It is observed that multiple proteins sense cadmium and can respond to its presence. Concerted action of all the proteins may be essential to realize full response against cadmium presence in soil and mitigation of plant growth inhibition. Better understanding of the response to cadmium stress would pave way for designing effective breeding strategies for pyramiding beneficial alleles in elite germplasm.